Lithium acts to modulate abnormalities at behavioral, cellular, and molecular levels in sleep deprivation‐induced mania‐like behavior. (18th October 2019) - Andrabi, Mutahar; Andrabi, Muatar Maknoon; Kunjunni, Remesh; Sriwastva, Mukesh Kumar; Bose, Samrat; Sagar, Rajesh; Srivastava, Achal Kumar; Mathur, Rashmi; Jain, Suman; Subbiah, Vivekanandhan
Abstract: Background: Ample amount of data suggests role of rapid eye movement (REM) sleep deprivation as the cause and effect of mania. Studies have also suggested disrupted circadian rhythms contributing to the pathophysiology of mood disorders, including bipolar disorder. However, studies pertaining to circadian genes and effect of lithium treatment on clock genes are scant. Thus, we wanted to determine the effects of REM sleep deprivation on expression of core clock genes and determine whether epigenetics is involved. Next, we wanted to explore ultrastructural abnormalities in the hippocampus. Moreover, we were interested to determine oxidative stress, tumor necrosis factor‐α (TNF‐α), and brain‐derived neurotrophic factor levels in the central and peripheral systems. Methods: Rats were sleep deprived by the flower pot method and were then analyzed for various behaviors and biochemical tests. Lithium was supplemented in diet. Results: We found that REM sleep deprivation resulted in hyperactivity, reduction in anxiety‐like behavior, and abnormal dyadic social interaction. Some of these behaviors were sensitive to lithium. REM sleep deprivation also altered circadian gene expression and caused significant imbalance between histone acetyl transferase/histone deacetylase (HAT/HDAC) activity. Ultrastructural analysis revealed various cellular abnormalities. Lipid peroxidation and increased TNF‐α levels suggested oxidative stress and ongoing inflammation. Circadian clock genes were differentially modulated with lithium treatment and HAT/HDAC imbalance was partially prevented. Moreover, lithium treatment prevented myelin fragmentation, disrupted vasculature, necrosis, inflammation, and lipid peroxidation, and partially prevented mitochondrial damage and apoptosis. Conclusions: Taken together, these results suggest plethora of abnormalities in the brain following REM sleep deprivation, many of these changes in the brain may be target of lithium's mechanism of action.